Utilidad de la glicemia a la admisión en la unidad de cuidados intensivos pediátrica como predictor de mortalidad de los pacientes hospitalizados en el Instituto Nacional de Salud del Niño, 2012-2013 - Toro Polo, Luis Miguel (2016)
Introduction. There is a high prevalence of mortality in the Pediatric Intensive Care Units (PICU) in developing countries. Association has been found between disglyce mia and mortality in the PICU; however, there is a lack of standardization of the utility of such ranges. Objectives. To analyze the association between glycemia levels in PICU admission and mortality in patients hospitalized at Instituto Nacional de Salud del Niño (INSN). Methods. Retrospective cohort in PICU patients admitted to INSN between 2012 and 2013. A Poisson regression model with robust variance was used to quantify the association. Diagnostic Test performance evaluation was used to describe sensitivit y, specificity, positive predictive value, negative predictive value and likelihood ratios for each range of glycemia. Results. 552 patients were included (Age range 5 to 79,8 months). The mean glycemia on admission was 121.3 mg/dL. Ninety two (16.6%) patients died during hospitalization. In multivariable analyses, significant associatio ns between glycemia <65 mg/dL (RR: 2.01, 95%CI 1.14-3.53), glycemia >200 mg/dL (RR: 2.91, 95%CI 1.71-4.55), malnutrition (RR: 1.53, 95%CI 1.04-2.25), mechanica l ventilation (RR: 3.71, 95%CI 1.17-11.76) and mortality at discharge were found. There was low sensitivity (between 17.39% and 39.13%) and high specificity (between 49.13% and 91.74%) for different glucose cut-off levels. Conclusions. There is an increased risk of death at discharge in patients who developed hypoglycemia and hyperglycemia on admission to the PICU. Certain glucose ranges (>200mg/dL and <65mg/dL) have a high specificity as predictors of death at discharge.